2003
DOI: 10.1149/1.1595665
|View full text |Cite
|
Sign up to set email alerts
|

Deep Levels in Oxygenated n-Type High-Resistivity FZ Silicon before and after a Low-Temperature Hydrogenation Step

Abstract: The behavior of oxygen in oxygen-doped high-resistivity (HR) n-type float-zone (FZ) silicon has been studied using a combination of analytical techniques. In the as-doped material, a large number of deep levels have been observed with deep-level transient spectroscopy. The corresponding parameters (concentration, activation energy, and trap signature) are given, and the possible identity is discussed in view of the presence of oxygen and other impurities in the material. In addition, the impact of a low-temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 40 publications
(61 reference statements)
2
1
0
Order By: Relevance
“…Although deep levels, similar to those observed in the present study, have been reported previously in as-grown high-resistivity FZ-Si [15][16][17][18][19], little is known on the exact origin of these centres. Firstly, it was suggested that a level at E c − 0.49 eV, where E c is the conduction band edge, is related to Si self-interstitials [15,16].…”
Section: Discussionsupporting
confidence: 90%
“…Although deep levels, similar to those observed in the present study, have been reported previously in as-grown high-resistivity FZ-Si [15][16][17][18][19], little is known on the exact origin of these centres. Firstly, it was suggested that a level at E c − 0.49 eV, where E c is the conduction band edge, is related to Si self-interstitials [15,16].…”
Section: Discussionsupporting
confidence: 90%
“…A similar trap (at E C -E T = 73 meV) in FZ-silicon was reported also in Ref. (21), but there the trap was not stable above 350 °C, which makes an accordance implausible. Trap B1: Trap B1 was detected for a proton dose of 3×10 13 cm -2 and within an annealing temperature range of 350-400 °C.…”
Section: Deep-level Defects In Proton Irradiated and Annealed Siliconsupporting
confidence: 79%
“…SRP, I-V, and DLTS measurements are performed, the details of the plasma exposure and measurements can be found in previous reports [26,29,30]. After being ultrasonically cleaned in acetone and methanol and dipped in a 1% HF solution, the silicon wafers are exposed to hydrogen plasma in a plasma-enhanced chemical vapor deposition (PECVD) system.…”
Section: Methodsmentioning
confidence: 99%